The Extended Metaphor of «Deng Xiaoping’s Cat» as a Text-Forming Resource (Based on the Material of the Spanish-Language Media) - Y. P. Murzin (Ибероамериканские тетради)
The famous Chinese proverb It doesn’t matter if a cat is black or white, as long as it catches mice is a predicative universal autosemantic metaphorical aphorism. Elevated by Deng Xiaoping to the level of a model for transforming the economy and society, it is now widely used in media discourse as a powerful tool for achieving cognitive, communicative and pragmatic goals by skillfully adapting to the contextual environment. It seems relevant to consider how this metaphor functions as a text-forming tool using examples from modern Spanish-language analytical publications. In the analyzed materials, the text-forming function of a metaphor is revealed through its deployment, through a number of metaphorically used words representing a group of thematically related lexical units: the phrase cat of Deng Xiaoping, which is used metaphorically, associatively serves as the basis for developing the content of other words that convey a metaphorical image. In a passage of particular length or in an entire text, in the course of describing real events or actions, the metaphor of the cat unfolds in the form of interspersed links of the thematic chain, which serve as components of the basic metaphor or thematically related lexical units, becoming a kind of metaphorical statement and characterization of actions and circumstances, summarizing the meaning of the text and acting as the author’s subjective personal assessment. In each case, the links of the chain are lexically and grammatically extended. The cats themselves can also be characters of the narrative, denoting, like the heroes of animal fables, certain power structures or subjects of economic activity. The results of the study are of considerable interest, since the original metaphorical microtext is an effective text-forming resource that contributes to the actualization of metaphorical and pragmatic meanings.